Penerapan AI , IoT, dan CPS dalam Industri Manufaktur Menuju Efisiensi Operasional - Balkhi Razzas Qasvini; Osin Lirfaija Salamanang; Muhamad Arya Ananda; Elia Setiana (JUSTIFY : Jurnal Sistem Informasi Ibrahimy, 2026)
In an era of exponential industrial transformation, the integration of advanced technologies has evolved into a key strategic asset for manufacturing organizations. Speed and accuracy in production lines and supply chain management have become critical factors in maintaining a competitive edge in volatile markets. This research article aims to critically analyze and synthesize the role of Information Technology (IT) integration—specifically Artificial Intelligence (AI), the Internet of Things (IoT), and Cyber-Physical Systems (CPS)—in mitigating operational risks and improving production process efficiency. Using a descriptive-qualitative analysis approach based on a systematic literature review, this article examines how IT infrastructure influences an organization’s production architecture. The results of the analysis show that the implementation of AI- and IoT-based IT can reduce machine maintenance costs by up to 35%, increase the accuracy of predictive maintenance to 92%, and transform operational methodologies from traditional reactive maintenance to data-driven maintenance